La vie des Gommes : pour une approche biographique des pneus de Carol Rama - Carolina Spovieri (Les Cahiers de l'École du Louvre)
Biographical events often seemed to motivate the works of Carol Rama (1918–2015). The rubber strips used in the Rubbers series (1970) are, for example, presented as the inner tubes of old bicycle tyres from her father’s factory. If these rubber strips have aroused any interest, it has generally been to study them from the point of view of Rama’s past, by bringing them back to the family tragedy of her father’s suicide. But if we move beyond this biographical approach, leaving behind the life of the artist to follow the historical trajectory of rubber strips (the ordinary use and function of the tyre, its use as an artistic material), it becomes possible to raise new hypotheses for reading the work in a different way. First, while the commercial origin of the object points to its perishable nature, the worn state of the tyre also tells us something about the artist’s choice to incorporate it into her work, as someone who loves “things that make a living” (Vergine, 1985). By stripping it of its status as an unusable commodity, the creative gesture gives the waste a kind of new memory, like a second life that makes it autonomous. Similarly, the ageing process of the tyre, which features prominently in the series, could ironically point to the short life of the objects of the bourgeois society from which Rama came, and simultaneously indicate the obsolescence of the medium itself, as the object replaces paint. Moreover, the Rubbers could contain “the crisis of the painting as a normal institution in the painting of our past” (Sanguineti, 1994). Taking seriously the multiple factors that contribute to tracing the life of these rubber strips would allow us to reflect on the interpretative dimensions of art based on the biography of the materials and not just that of the artist.